A failsafe for voters? Cast and rejected provisional ballots in North Carolina - Merivaki, Thessalla and Smith, Daviel A. (Political Research Quarterly)
Provisional ballots constitute a failsafe for voters who have their registration or voter identification questioned by poll workers. Scholars have yet to examine who is more likely to cast a provisional ballot, and more importantly, why some provisional ballots are rejected. We suggest that beyond individual-level factors, there are administrative reasons why some prospective voters are more likely to be required to cast provisional ballots than others, and why some provisional ballots are rejected. Drawing on county data collected by the U.S. Election Assistance Commission$1 (Bs (EAC) biennial Election Administration and Voting Surveys (EAVS) from 2012 to 2016, and individual records of provisional ballots cast in the 2016 Presidential Election in North Carolina, we examine aggregate- and individual-level reasons to explain who casts provisional ballots and why some are rejected. Our findings raise normative questions concerning whether voters casting provisional ballots are treated equally under the law.- Reproduced s
Keywords: Provisional ballots, Election administration, HAVA, U.S. Election assistance commission, North Carolina